Chemical structure of the arabinogalactan protein from gum ghatti and its interaction with bovine serum albumin. (6th March 2015) - Ghosh, Kanika; Ray, Sayani; Ghosh, Debjani; Ray, Bimalendu
Highlights: A highly branched arabinogalactan protein could be isolated from A. latifolia gum. The backbone of this compound contained Gal, Ara, and GlcA residues. This compound could form a water soluble electrostatically driven complex with BSA. A novel strategy based on ESMS analysis of peracetylated oligomers was developed. Abstract: Exudate gums, because of their beneficial properties, have been significant items of international trade in various industries for centuries. This manuscript sets out to gain insight into the fine structural details of an arabinogalactan protein (AGP) of gum ghatti ( Anogeissus latifolia gum). The presence of a highly branched 554 kDa AGP having 1, 6-linked Gal p, 1, 2-linked Man p, 1, 3-linked Ara f and 1, 4-linked Glc p A main chain, substituted at O -4, 6 of 1, 2-linked Man p, and O -3/ O -3, 4 of 1, 6-linked Gal p residues by Ara f, Ara p and Gal p units was revealed by chemical, chromatographic, ESMS, and NMR analyses. In particular, ESMS analysis of per acetylated oligomeric fragments derived from AGP by Smith degradation followed by acetylation was described as a commanding tool for providing critical structural information on a spectrum of glycerol tagged oligosaccharides. In addition, formation of an electrostatically driven complex between the isolated AGP and bovine serum albumin resulting in changes in the microenvironment around the tryptophan residues of BSA was established. A moderate radical scavenging activity comparable with those of standard antioxidants was observed from the AGP fraction (∼94% at 1 mg/mL) that could be valuable in foods or pharmaceutical products as alternatives to synthetic antioxidants.